2023
DOI: 10.1186/s12986-023-00733-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of DASH diet on glycemic response, meta-inflammation and serum LPS in obese patients with NAFLD: a double-blind controlled randomized clinical trial

Abstract: Background As dietary approaches to stop hypertension (DASH) dietary pattern has been shown to be effective in hypertension and obesity, the present study investigated the effects of following DASH diet on glycemic, meta-inflammation, lipopolysaccharides (LPS) and liver function in obese patients with non-alcoholic fatty liver disease (NAFLD). Methods In this double-blind controlled randomized clinical trial, 40 obese patients with NAFLD were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…(2) Studies on the treatment of NAFLD. Many pieces of evidence showed that calorie restriction ( 18 , 19 ), fat restriction ( 20 , 21 ), carbohydrate reduction ( 22 , 23 ), and appropriate vitamin supplementation ( 24 , 25 ) in diet therapy, aerobic exercise ( 26 , 27 ) resistance exercise ( 28 , 29 ) and high-intensity interval training ( 30 ) in exercise therapy had good therapeutic effects. Moreover, clinical experiments have proved that combining diet and exercise may achieve better therapeutic efficacy than a single one ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Studies on the treatment of NAFLD. Many pieces of evidence showed that calorie restriction ( 18 , 19 ), fat restriction ( 20 , 21 ), carbohydrate reduction ( 22 , 23 ), and appropriate vitamin supplementation ( 24 , 25 ) in diet therapy, aerobic exercise ( 26 , 27 ) resistance exercise ( 28 , 29 ) and high-intensity interval training ( 30 ) in exercise therapy had good therapeutic effects. Moreover, clinical experiments have proved that combining diet and exercise may achieve better therapeutic efficacy than a single one ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of a Dash diet is also beneficial for improving inflammatory markers. Rooholahzadegan et al (2023) showed a decrease in body weight, BMI, serum triglycerides, very low-density lipoprotein cholesterol (VLDL-C), MCP-1, and improvements in total antioxidant capacity (TAC) and glutathione (GSH).…”
Section: Effect Of Diet Modification In Inflammation and Oxidative St...mentioning
confidence: 99%
“…Dash diets also contain high levels of Ca and Mg. Calcium and magnesium are inversely related to obesity because of their role in increasing lipolysis, thus playing an important role in weight management. Calcium and magnesium are also known to be protective agents against DNA damage and antioxidant enzymes because they influence oxidative stress levels by increasing TAC and GSH as free radical scavengers (Rooholahzadegan et al, 2023). The mechanism of the benefits of the MedDiet and dash diet in reducing inflammation and oxidative stress is presented in Figure 1.…”
Section: Effect Of Diet Modification In Inflammation and Oxidative St...mentioning
confidence: 99%
“…Therefore, LPS binds to LPS-binding proteins and then binds to TLR-4, triggering insulin resistance, followed by an immune response and greater propensity for inflammation; that is, LPS increases the levels of gut-derived TLR4 since this receptor is activated in hepatic Kupffer cells and stellate cells. Further pro-inflammatory and pro-fibrotic pathways are stimulated through several cytokines, including IL1, IL6, and TNF [77,[131][132][133][134]. In MAFLD, TLR-4 signaling initiates local inflammatory changes and develops hepatic steatosis.…”
Section: Brain-gut-liver Axismentioning
confidence: 99%